2016
DOI: 10.1371/journal.pone.0149547
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of Task-Based fMRI for Preoperative Planning: A Test-Retest Study in Brain Tumor Patients and Healthy Controls

Abstract: BackgroundFunctional magnetic resonance imaging (fMRI) continues to develop as a clinical tool for patients with brain cancer, offering data that may directly influence surgical decisions. Unfortunately, routine integration of preoperative fMRI has been limited by concerns about reliability. Many pertinent studies have been undertaken involving healthy controls, but work involving brain tumor patients has been limited. To develop fMRI fully as a clinical tool, it will be critical to examine these reliability i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 58 publications
(73 reference statements)
0
44
0
Order By: Relevance
“…However, the majority of studies report higher reproducibility for signal magnitude measures compared to signal extent measures (Adcock et al, 2003; Jansen et al, 2006; Harrington, Buonocore & Farias, 2006; Morrison et al, 2016). Importantly, Jansen et al (2006) reported that a magnitude measure determined dominance reproducibly only when just those voxels that exceeded a criterion activation level were included; an extent measure was not reproducible.…”
Section: Resultsmentioning
confidence: 99%
“…However, the majority of studies report higher reproducibility for signal magnitude measures compared to signal extent measures (Adcock et al, 2003; Jansen et al, 2006; Harrington, Buonocore & Farias, 2006; Morrison et al, 2016). Importantly, Jansen et al (2006) reported that a magnitude measure determined dominance reproducibly only when just those voxels that exceeded a criterion activation level were included; an extent measure was not reproducible.…”
Section: Resultsmentioning
confidence: 99%
“…The LI was calculated based on suprathreshold voxel count (i.e., extent) rather than intensity of activation. The reproducibility and robustness of both methods have been tested and debated (Jansen et al, 2006; Morrison et al, 2016; Seghier, 2008). The extent approach used is more appropriate for large region of interests (ROIs) (Jansen et al, 2006), allowing for inter‐individual variability in morphology and in activation location as is possible for children with UCP (Wittenberg, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…The spatial overlap between runs was determined by masking LI datasets of run 1 with subsequent runs for each leg. The total number of activated voxels were counted for each run (V Run1 ; V Run2 ), and then the number of commonly activated voxels were determined (V overlap ) using a Dice coefficient (Dice, 1945; Morrison et al, 2016) according to the following formula:Roverlap=true[true(2*Voverlaptrue)true(VRun1+VRun2true)true]…”
Section: Methodsmentioning
confidence: 99%
“…SWG task activates mainly frontal lobe language and cognitive support areas but are less consistent activators of temporal language regions (Pillai & Zaca, ; Zaca et al, ; Zaca, Jarso, & Pillai, ). These tasks are often repeated to confirm the reproducibility of activations (Carp, ; Fernández et al, ; Harrington, Buonocore, & Tomaszewski Farias, ; Maïza et al, ; Morrison et al, ; Poline, Strother, Dehaene‐Lambertz, Egan, & Lancaster, ; Rutten, Ramsey, van Rijen, & van Veelen, ; Voyvodic, ). Previous validation studies evaluated across‐subject reproducibility; however, within‐subject repeatability in the same scan session for reproducibility of language lateralization and localization has not yet been comprehensively validated.…”
Section: Introductionmentioning
confidence: 99%
“…In general, reliability metrics are used to quantify test–retest variability of activation clusters across sessions and across subjects (Gorgolewski, Storkey, Bastin, Whittle, & Pernet, ; Otzenberger, Gounot, Marrer, Namer, & Metz‐Lutz, ; Raemaekers, Du Plessis, Ramsey, Weusten, & Vink, ). Previous studies reported varied results due to the varied statistical methods used to quantify test–retest reliability (Chen & Small, ; Fesl et al, ; Morrison et al, ). The majority of studies used correlation coefficients as a prominent measure of reliability which informs about the consistency of activation between subjects (Caceres, Hall, Zelaya, Williams, & Mehta, ; Maldjian, Laurienti, Driskill, & Burdette, ; Stevens, Clarke, Stroink, Beyea, & D'Arcy, ).…”
Section: Introductionmentioning
confidence: 99%